Sustainable biogas production: energy potential and storage aspects - Narayanaswamy, Narendra; Muhamad, Mat Noor; Reddy, Chethan Mariyanna Adinarayana (SPRINGER HEIDELBERG, 2025)
Lignocellulosic biomass has drawn interest recently as a potential anaerobic digestion substrate for producing sustainable biogas. This study investigates the possibilities for producing biogas from various organic wastes, such as cashew fruit, cow dung, silkworm larval litter, and cattle urine materials that are abundant, inexpensive, and high in lignin and carbon. Anaerobic digestion was carried out with various combinations of these substrates at mesophilic temperatures (35 °C). The maximum amount of biogas and methane was produced when 20% cow dung, 40% silkworm larval litter, 30% water, and 10% cow urine were co-digested. Process consistency was demonstrated by the experimental findings, which showed a maximum biogas output of 6.99 m3 with a standard deviation of 0.295. The biogas calorific value was 35.1 MJ/m3, and its maximum methane content was 66.7%. The study suggests more optimisation to increase methane output and storage efficiency while highlighting the potential of these biomass resources for localized energy applications.